2015
DOI: 10.4172/2162-6359.1000298
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Neutrality of Money towards Real Output: A Case of Malaysia

Abstract: On the theoretical ground, Keynesian believes pricing mechanism work better than government intervention, which comprised the Keynesian's 'invincible hand' in the market. Price equilibrium restores automatically, therefore, floating exchange rate regime, in which exchange rate is determined by the market force of demand and supply, is viewed as the optimum exchange rate regime to be implemented. Furthermore, floating exchange rate regime comes with high stability of real exchange rates. However McKinnon, et al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…The results indicated that monetary growth has had a positive impact on inflation in Vietnam, and that inflation has been increasing for three months in response to a positive shock to monetary growth and had no impact on production, budget deficit growth, and interest rate. Sam and Geetha [41] examined the long-run behavior of monetary aggregates towards the Malaysian economy based on quarterly data ranging from 1996 to 2014. In this paper, the unanticipated money supply was tested under the vector error correction model (VECM).…”
Section: Theoretical Foundations and Literature Reviewmentioning
confidence: 99%
“…The results indicated that monetary growth has had a positive impact on inflation in Vietnam, and that inflation has been increasing for three months in response to a positive shock to monetary growth and had no impact on production, budget deficit growth, and interest rate. Sam and Geetha [41] examined the long-run behavior of monetary aggregates towards the Malaysian economy based on quarterly data ranging from 1996 to 2014. In this paper, the unanticipated money supply was tested under the vector error correction model (VECM).…”
Section: Theoretical Foundations and Literature Reviewmentioning
confidence: 99%